Interleukin-2, Interferon-gamma Gene Polymorphisms in Recurrent Aphthous Stomatitis - Shamsolmoulouk Najafi; Hila Yousefi; Mahsa Mohammadzadeh; Alireza Zare Bidoki; Elham Farhadi; Nima Rezaei (Prague Medical Report, 2017)
Recurrent aphthous stomatitis (RAS) is the most common oral ulcerative inflammatory disease with unknown etiology. IL-2 and IFN-γ are secreted by Th1 cells and the elevated levels of them have been reported in RAS. Single nucleotide polymorphisms (SNPs) of IL-2 and IFN-γ genes could alter the cytokine production. The aim of this study was to investigate frequencies of IL-2 and IFN-γ alleles and genotypes in a group of patients with minor-RAS (MiRAS). PCR-SSP method used to type genomic DNA of 64 Iranian patients with MiRAS for IL-2 gene (G –330 T) and (G +166 T) and IFN-γ gene at position UTR5644 (A/T). Frequency of each allele and genotype was compared with control group. IL-2 +166 G allele was significantly lower among patients which was reflected in significantly decreased of GG genotype at this position, while IL-2 +166 T allele was significantly higher among patients, IL-2 GT genotype was also significantly higher in RAS patients. No significant differences were found regarding IL-2 –330 G/T allele frequencies, while IL-2 GT genotype at this position was significantly higher among patients and IL-2 –330 TT genotype was significantly lower among RAS patients. Although no significant differences were found in IFN-γ allele frequencies at UTR5644 (A/T), AT genotype at this position was significantly overrepresented among patients compared with controls. Results of this study suggest that certain SNPs of IL-2 and IFN-γ genes have association with predisposition of individuals to RAS. More studies in different ethnic groups are needed to confirm results of this study.